QUANTUMBOX - SAFE AND PRIVATE EMAIL WITH QUANTUM ENCRYPTION - Muthyala Pavani,; Dr. BNV Madhu Babu, (Utilitas Mathematica, 2025)
Though an evolution-like speed describes quantum computing, it serves as one of the threats to traditional cryptographic systems, especially concerning email communication. The Quantum Secure Email Client Application (QSECA) is introduced here as a strong enough solution for protecting email content against future potential quantum threats. QSECA provides security on email communications with quantum-resistant encryption mechanisms, among which the most sophisticated are the Quantum Key Distribution (QKD) protocols, thus ensuring confidentiality, integrity, and authenticity to the recipient. Digital signature, multi-factor authentication, and encryption key management raise protection against adversarial acts such as spoofing, phishing, and any unauthorized intrusion into confidential information. A very convenient user interface and compatibility with established email systems, accompanied by additional security features such as secure transmission protocols and status notifications, help to preserve communications. The future development of QKD systems considered scalability and secure long-distance communication through the satellite route, which would have a direct impact on global network security. Other future development pathways include hybridization with post-quantum cryptographic algorithms and the use of blockchain technology for guarantees regarding data integrity, supported with possible intrusion detection from machine learning or AI. Thus, being a futuristic solution for email security, QSECA provides a fertile ground for individuals and organizations to further develop countermeasures against quantum security threats. Moreover, the paper delves into future development concerning integration into regulatory compliance standards and enhanced privacy mechanisms to satisfy evolving global data protection messages.